The effect of rest interval length on bench press performance with heavy vs. light loads - Willardson, J. M.; Burkett, L. N. (The Journal of Strength and Conditioning Research, 2006)
The purpose of the current study was to compare the effect of 3 different rest intervals on multiple sets of the bench press exercise performed with heavy vs. light loads. Sixteen resistance-trained men performed 2 testing sessions each week for 3 weeks. During the first testing session each week, 5 consecutive sets of the bench press were performed with 80% of 1 repetition maximum (1RM) and with a 1-, 2-, or 3-minute rest interval between sets. During the second testing session each week the same procedures were repeated with 50% of 1RM. The total repetitions completed and the sustainability of repetitions were compared between rest conditions and between loads. For each load, resting 3 minutes between sets resulted in significantly greater total repetitions vs. resting 2 minutes (p = 0.000) or 1 minute (p = 0.000) between sets. However, the sustainability of repetitions was not significantly different between loads (p = 0.849). These results can be applied to weekly bench press workouts that undulate between heavy (i.e., 80% 1RM) and light (i.e., 50% 1RM) intensities. When the training goal is maximal strength development, 3 minutes of rest should be taken between sets to avoid significant declines in repetitions. The ability to sustain repetitions while keeping the intensity constant may result in a higher training volume and consequently greater gains in muscular strength.